One-factor-Garch models for German stocks: Estimation and forecasting - Thomas Kaiser (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1996)
This paper presents theoretical models and their empirical results for the return and variance dynamics of German stocks. A factor structure is used in order to allow for a parsimonious modeling of the first two moments of returns. Dynamic factor models with GARCH dynamics (GARCH(1,1)-M, IGARCH(1,1)-M, Nonlinear Asymmetrie GARCH(1,1)-M and Glosten-Jagannathan-Runkle GARCH(1,1)-M) and three different distributions for the disturbances (Normal, Student's t and Generalized Error Distribution) are considered, Out-of-sample forecasts for the stock returns based upon these models are computed. These forecasts are compared with forecasts based on individual GARCH(1,1)-M models, static factor models, naive, random walk and exponential smoothing forecasts.
Keywords: C32; G12; 330; Dynamic Factors; GARCH; Asset Pricing; Forecasting; Börsenkurs; Aktienmarkt; CAPM; Schätztheorie; Theorie; Deutschland